Aesthetic and Myth in the Poetry of Keats - Evert, Walter H. (Book collections on Project MUSE., 1965)
In this highly perceptive and original study Evert traces Keats' formulation in his early work of mythography of the imagination founded on Apollo through its radical qualification in his later work. Originally published in 1965. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.